Determinants of customer satisfaction with hospitals: a managerial model - Andaleeb, Syed Saad (© 1998 Published by MCB UP Ltd., 2016)
This article was published in the International Journal of Health Care Quality Assurance [© 1998 Published by MCB UP Ltd. ] and the definite version is available at: http://dx.doi.org/10.1108/09526869810231541 The Journal's website is at: http://www.emeraldinsight.com/doi/abs/10.1108/09526869810231541